Real Estate Price Prediction (International Journal of Innovative Research in Computer Science & Technology, 2020)
Analysing various fields, associate  numbers, events became the need of time and most  important step to do anything and hence data science  became an important part in every field. Using the  concept of data science, the project of Real Estate Price  Prediction is built. The motive of creating a project on  Real Estate Price Prediction was just to implement the  concepts of data science and python language that is used  in analysing for designing an application. This was done  to get better understanding of the skills that are needed in python language, analysis using data science. The project  focuses on the different features and algorithm available  in python and data science. In this project various library  of python is used to design an attractive, effective, and beautiful project. The project will introduce a Real Estate  price estimation system that done estimate based on various mathematical algorithms and tricks and then gives  best possible result.So basically, what this application  does is identify the need of user in any specific area in  Bangalore.
Keywords: Data science; Analysis; Price; Estimation; Bangalore